2014
DOI: 10.1128/aac.02329-13
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Cross-Linking in Glycopeptide-Resistant Actinomycetales

Abstract: Synthesis of peptidoglycan precursors ending in D-lactate (D-LacThe second glycopeptide resistance mechanism has been detected in mutants of E. faecium selected in vitro that are resistant to high levels of glycopeptides (MICs of Ͼ1,000 g/ml) by the production of the metallo-D,D-carboxypeptidase DdcY in the absence of the production of precursors ending in 18). This enzyme eliminates the target of glycopeptides from peptidoglycan precursors by hydrolysis of the C-terminal D-Ala residue of pentapeptide stems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
(59 reference statements)
0
32
0
Order By: Relevance
“…Rather, lipid II amidation appeared to strongly decrease vancomycin binding affinity, both in the in vitro system and as revealed by the determination of binding parameters. Earlier studies suggested a correlation between vancomycin resistance and the reduced degree of peptidoglycan amidation in S. aureus strain Mu50, and inducible amidation of D-iso-Glu has been reported in Clostridium difficile and Streptomyces coelicolor A3(2), but not in glycopeptide-resistant enterococci (55)(56)(57)(58)(59)(60)(61). Moreover, it was shown that the antimicrobial activity of vancomycin is antagonized more efficiently by short synthetic peptides (55,62).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, lipid II amidation appeared to strongly decrease vancomycin binding affinity, both in the in vitro system and as revealed by the determination of binding parameters. Earlier studies suggested a correlation between vancomycin resistance and the reduced degree of peptidoglycan amidation in S. aureus strain Mu50, and inducible amidation of D-iso-Glu has been reported in Clostridium difficile and Streptomyces coelicolor A3(2), but not in glycopeptide-resistant enterococci (55)(56)(57)(58)(59)(60)(61). Moreover, it was shown that the antimicrobial activity of vancomycin is antagonized more efficiently by short synthetic peptides (55,62).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance profiles were therefore determined by the differences between the amino acid sequences of the VanR-VanS proteins present rather than by inherent differences in cell wall structure or biosynthesis between the strains. The activity of extracellular D,D-carboxypeptidases has been shown to alter the efficacy of glycopeptide antibi- (39), but the difference in the control by VanR-VanS is clearly the dominant factor differing between S. coelicolor and S. toyocaensis. The incomplete restoration of resistance to vancomycin in S. toyocaensis H2360 (⌬vanRSst vanRSsc) compared to the level of resistance of wild-type S. coelicolor could, however, suggest some contribution from differences in carboxypeptidase activity between strains, but this could also be due to a possible increase in the level of expression of staP from the A47934 cluster, which is known to have deleterious effects on growth (29).…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the PG composition of a range of bacteria has revealed that LDTs are more prevalent than expected, especially among Actinomycetales, which show the following percentages of 3¡3 cross-links: 60 to 80% in mycobacteria, 38% in Corynebacterium jeikeium (41,44), 57% in S. coelicolor, and 49% (exponential phase) to 31% (stationary phase) in Nonomuraea sp. ATCC 39727 (45).…”
Section: Discussionmentioning
confidence: 99%